2017
DOI: 10.1016/j.clcc.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Direct Health Care Costs for Metastatic Colorectal Cancer Patients Treated With Cetuximab or Bevacizumab-containing Regimens in First-line or First-line Through Second-line Therapy

Abstract: PPPM total health care costs for 1L and 2L therapy tended to be greater for patients treated with 1L CET-containing regimens than for 1L BEV-containing regimens. Also, continuing treatment with BEV-containing regimens 1L-2L was less costly than switching between BEV and CET. The cost differences between BEV and CET hold important implications for treatment decisions of mCRC patients in real-world clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…However, treatment costs are increased substantially when a monoclonal antibody is added to conventional treatment, for example adding bevacizumab increases the cost per cycle by €811,31 and cetuximab by €1342,73. This result is in line with previous studies that show a lower cost of first-and second-line treatment with bevacizumab-containing regimens in comparison to cetuximab-containing regimens despite a similar efficacy [55][56][57][58]. This cost difference has shown to be more than $2000 per month per patient and alludes to a better value offering for funders [55][56][57][58].…”
Section: Discussionsupporting
confidence: 90%
“…However, treatment costs are increased substantially when a monoclonal antibody is added to conventional treatment, for example adding bevacizumab increases the cost per cycle by €811,31 and cetuximab by €1342,73. This result is in line with previous studies that show a lower cost of first-and second-line treatment with bevacizumab-containing regimens in comparison to cetuximab-containing regimens despite a similar efficacy [55][56][57][58]. This cost difference has shown to be more than $2000 per month per patient and alludes to a better value offering for funders [55][56][57][58].…”
Section: Discussionsupporting
confidence: 90%
“…The study of real-world direct health care costs in mCRC patients in the United States showed that the average cost of cancer regimen per month was USD 13,646 if bevacizumab in the first line and cetuximab in the second line had been administered, which presented 60% of the total costs. Similarly, the average cost per month was USD 12,773 if bevacizumab in the first line and panitumumab in the second line had been used [18]. However, direct costs in the Czech Republic and USA are not comparable due to different socioeconomic status and distinctions in a way of reimbursement of health care.…”
Section: Costs Of Mcrc Treatmentmentioning
confidence: 99%
“…Isoprenoids are lipid compounds found in nature and they have many important functions (8,9). The enzymes that synthesize and use isoprenoids are among the most important drug targets for the treatment of cardiovascular disease, osteoporosis and bone metastases and have shown promise as antimicrobials (10)(11)(12). The five carbon (C5) precursors of isoprenoids, isopentenyl diphosphate (IPP) and dimethylallyl diphosphate (DMAPP) (Fig.…”
Section: Introductionmentioning
confidence: 99%